Long-term p110α PI3K inactivation exerts a beneficial effect on metabolism - Foukas, Lazaros C (WILEY-VCH Verlag, 2013)
The insulin/insulin-like growth factor-1 signalling (IIS) pathway regulates cellular and organismal metabolism and controls the rate of aging. Gain-of-function mutations in p110α, the principal mammalian IIS-responsive isoform of PI 3-kinase (PI3K), promote cancer. In contrast, loss-of-function mutations in p110α impair insulin signalling and cause insulin resistance, inducing a pre-diabetic state. It remains unknown if long-term p110α inactivation induces further metabolic deterioration over time, leading to overt unsustainable pathology. Surprisingly, we find that chronic p110α partial inactivation in mice protects from age-related reduction in insulin sensitivity, glucose tolerance and fat accumulation, and extends the lifespan of male mice. This beneficial effect of p110α inactivation derives in part from a suppressed down-regulation of insulin receptor substrate (IRS) protein levels induced by age-related hyperinsulinemia, and correlates with enhanced insulin-induced Akt signalling in aged p110α-deficient mice. This temporal metabolic plasticity upon p110α inactivation indicates that prolonged PI3K inhibition, as intended in human cancer treatment, might not negatively impact on organismal metabolism.